Estimation of chloride diffusion coefficient from water permeability test of cementitious materials. (18th July 2022) - Xie, Jianhe; Wang, Junjie; Li, Molan; Xu, Lei; Xiang, Dong; Wang, Yuli; He, Hang; Zhu, Yi; Zhao, Jinxia
Highlights: A theoretical model between Dss and k has been built and validated by experimental work: Dss / k  = 32 Daq / d 2 pore . ·Average pore diameter da is more fitted to the model than critical pore diameter dc . Applying this model could aid to predict the difficult-to-get Dss of cementitious materials through the rapid measurements of k and da . Abstract: Chloride diffusion coefficient of concrete is a critical parameter indicating a durability property of steel-reinforced concrete elements in chloride-laden environments. However, chloride diffusion tests of concrete could take months or even years to finish in order to obtain the steady state chloride diffusion coefficient ( Dss ). Most engineers have to take a rapid chloride migration test to get a chloride migration coefficient, which could still take one or a few days to finish. In contrast, a water permeability test could be finished within only a few hours, and a steady state water permeability coefficient ( k ) can be obtained. This study aims to build a theoretical model between Dss and k, and the model has been validated by experimental work. The obtained model shows that relationship between Dss (in m 2 /s) and k (in m 2 ) can be simply described using a formula Dss / k  = 32 Daq / d 2 pore, where Daq (in m 2 /s) is the chloride diffusion coefficient in free solution, and dpore (in m) is the equivalent pore diameter. The experimental validation work showed that the model is in good agreement with the measured data, and dpore in the formula can be replaced with the average pore diameter da . Applying this model in engineering projects could aid to predict the difficult-to-get Dss of cementitious materials through the rapid measurements of k and da .